The Architect's Role in Software Ecosystems Health - Amorin, Simone da Silva; McGregor, John D.; de Almeida, Eduardo Santana; Chavez, Christina von Flach (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2017: Anais do II Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software, 2017)
Software ecosystems have adopted many different strategies to achieve success and good health. The role of software architect is one of the main contributors to that success. Their activities are crucial for realizing the business strategy of their organization. Software ecosystems define multi-sided markets that require different strategies from a traditional two-sided market. The architectural practices in the multi-sided market must support the need for flexibility and rapid reaction. These new demands broaden our understanding of the software architect's role and the impact of their action on ecosystem structure. In particular the need to understand how to operate in a collaborative, cooperative environment to exploit competition. In this position paper, we discuss how software architect's actions influence the ecosystem health through their indicators: productivity, niche creation, and robustness.